Actualities in public investment: The current situation of “Invierte.pe” at two years from it’s released that caused that the Legislative Decree 1432 had to suffer some modifications - Gaviño Masías, Karla Mónica (2019)
It’s been two years since the National Multiyear Programming and Investment Management System came into force. During this time, the practical experience helped to identify different aspects of its creation rules that needed to be improved. This article reviews those aspects and its regulation, according to the modifications contemplated in the new Legislative Decree 1432. While the level of decentralization already in place by the SNIP and its focus on state-run services rather than the work itself may be debatable, the truth is that SNIP served as the basis for the construction of the National Multi-Year Programming System and Investment Gestion, which captures many of the successes of the System and attempts to improve other aspects that remained outstanding.